Suitability of bioenergy tree species on degraded peatlands in Central Kalimantan, Indonesia - Maimunah, S.; Rahman, S.A.; Samsudin, Y.B.; Artati, Y.; Simamora, T.I.; Andini, S.; Lee, S.M.; Baral, H. (Center for International Forestry Research, 2022)
Vast areas of degraded peatlands in Kalimantan need a sustainable longterm restoration mechanism, ideally one that can address energy security without compromising food production or biodiversity conversation. This research assesses the survivability and growth performance of potential bioenergy crops: gamal (Gliricidia sepium (Jacq.) Walp.), kaliandra (Calliandra calothyrsus Meissner), kemiri sunan (Reutealis trisperma (Blanco) Airy Shaw) and nyamplung (Calophyllum inophyllum L.), that could be cultivated to produce bioenergy and restore degraded peatlands. Parameters observed were tree height and stem diameter growth as well as plant survival rates. Trials was conducted on a two-hectare demonstration plot on burned degraded peatland in Buntoi village, Pulang Pisau district, Central Kalimantan province. Using a split plot design, two treatments were applied to each species, i.e., agroforestry (intercropped with Ananas comosus (L.) Merr.) and monoculture plantation. For each species, these treatments were replicated in two separate subplots. Results indicate nyamplung being the most adaptable species, followed by kemiri sunan, and both species performing better under agroforestry than monoculture treatments. Further study is needed to assess productivity and associated biofuel yields.